Municipalities, autonomy and coordination - Capdevila, Silvina Claudia (Universidad Nacional del Litoral, 2014)
The theme developed in the present text is the issue of the autonomy of the municipalities in the national Constitution of Argentina, and how the Argentine law deals with the problem of the "metropolitan areas" in small and medium-sized cities in the provinces.